Taxonomy, biology and population dynamics of moonfish mene maculata (bloch & schneider, 1801) occurring in cochin waters - Anju John (KUFOS, 2019)
Abstract- The taxonomy, biology and population dynamics of moonfish Mene maculata occurring along the Cochin waters were studied. Morphometric studies were based on 17 morphometric characters. The allometric coefficients of the morphometric characters and their relationship with fish size (SL) were estimated using linear regression model. DNA Barcodes were generated for the species and were subject to BLAST. The results showed that the 628 base pair sequence matched 100% with the earlier database of Mene maculata. Diagnostic characters and DNA barcoding confirms the occurrence of M. maculata in Cochin waters. Gut content analysis revealed that the species is poorly fed, with most of the fishes with an empty stomach. On analysis of the gut contents, it was found that only 19 guts had some food item in them. The major food organism encountered was shrimp larvae with Index of Preponderance value of 99.43, followed by fish larvae with 0.57. Gastro Somatic Index values are found to peak during the month of March. Gonado Somatic Index values worked out monthly for the species showed that the value peaked in the month of April, decreasing sharply to reach its lowest in September, indicating peak spawning period just after the month of April for the species. The peak spawning season of the species coincides more or less with the monsoon season. The average fecundity of M. maculata estimated was 10355. The average sex ratio between male and female observed during the period was 1.375 showing dominance of female over male. The size at first maturity for female is estimated to be 19.47cm and for the male it is 19.63. Length-weight relationships (LWRs) showed dissimilar growth pattern for males (b = 3.113) and females (b = 2.8059); males being isometric and female being negatively allometric. Growth pattern for the pooled data, b = 2.7832, showed negative allometric growth. The fishes were in a better condition/well-being during the months of October and November. The von Bertalanffy growth model for M. maculata in the Cochin waters was described as Lt = 245 (1-e-1.09(t+0.081555)). The longevity (tmax) of M. maculata from the present study was 2.67 years.